PERAN MEDIASI STRES AKADEMIK DALAM PENGARUH ANTARA EFIKASI DIRI AKADEMIK TERHADAP PROKRASTINASI AKADEMIK PADA MAHASISWA TINGKAT AKHIR - Nurmala, Nurmala; Allein, Nur Du; Wulandari, Meilisa (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2025)
Academic procrastination is a common behaviour among university students, especially those in their final year. One psychological factor believed to influence this tendency is self-efficacy—the belief in one’s ability to complete academic tasks. At the same time, educational stress may act as a psychological mechanism that bridges the relationship between self-efficacy and procrastination. This study aims to examine whether academic stress mediates the relationship between self-efficacy and academic procrastination. A total of 218 final-year university students in the Greater Jakarta area (JABODETABEK) participated in this study through accidental sampling. Data were collected using adapted versions of three standardized psychological instruments: the College Academic Self-Efficacy Scale (CASES) to measure self-efficacy, the Educational Stress Scale for Adolescents (ESSA) to assess educational stress, and the Tuckman Procrastination Scale (TPS) to evaluate academic procrastination. Data were analysed using path analysis to test the proposed mediation model. The results revealed that self-efficacy had a significant negative effect on academic stress (a = -0.167, p < 0.001) and academic procrastination (c = -0.152, p < 0.001). Furthermore, academic stress had a significant positive effect on academic procrastination (b = 0.91, p < 0.001). When academic stress was included as a mediating variable, the direct effect of self-efficacy on procrastination remained significant but was reduced (c’ = -0.229, p < 0.001), indicating a partial mediation. These findings suggest that academic stress serves as a mediator in the relationship between self-efficacy and academic procrastination. In other words, self-efficacy influences the tendency to procrastinate indirectly through its impact on academic stress. This highlights the importance of not only enhancing students’ academic self-efficacy but also implementing strategies to reduce academic stress in order to effectively minimize academic procrastination among final-year university students.